Pengaruh Pemberian Pupuk Organik Cair Nasa Dan Pupuk Kompos Terhadap Pertumbuhan Tanaman Kenaf ( Hibiscus cannabinus L) - Hairin Juanda; Tutik Nugrahini; Mahdalena Mahdalena (Agrifarm : Jurnal Ilmu Pertanian, 2018)
Effect of NASA Liquid Organic Fertilizer and Compost Fertilizer on Kenaf Plant Growth (Hibiscus cannabinus L). This study aims to determine the effect of NASA POC, compost fertilizer and the interaction of NASA POC and compost fertilizer on kenaf plants. This research was carried out at East Borneo Samarinda Indonesia. with a time of ± 4 months, starting from June to September 2016. The design of the study uses factorial completely randomized design (CRD) consisting of 2 treatments and 4 replications. The treatment consists of 2 factors. The first factor is the administration of NASA POC consisting of 4 levels, namely: j0: Control (without treatment), j1: POC with a concentration of 10 ml / liter of water, j2: POC with a concentration of 15 ml / liter of water, j3: POC with a concentration of 20 ml / liter of water. The second factor is Compost fertilizer consisting of 4 levels, namely: k0: Without the provision of Compost Fertilizer, k1: Composting 500 gram / polybag, k2: Composting Fertilizer 700 grams / polybag, k3: Composting 800 grams / polybag. From the analysis of variance showed that the effect of giving NASA POC (J), compost (K) and the interaction of NASA POC and compost (JK) did not affect the parameters of plant height 30 DAP, 60 DAP and 90 DAP, stem diameter 30 DAP, 60 DAP and 90 DAP, number of leaves 30 DAP, 60 DAP and 90 DAP, leaf area 30 DAP, 60 DAP and 90 DAP.